2000
DOI: 10.1128/iai.68.1.141-150.2000
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Immune Responses against T- and B-Cell Epitopes fromPlasmodium falciparumLiver-Stage Antigen 1 in Rodent Malaria Models and Malaria-Exposed Human Subjects in India

Abstract: Liver-stage antigen 1 (LSA-1) is a potential vaccine candidate against preerythrocytic stages of malaria. We report here the immunogenicity of linear synthetic constructs delineated as T H -cell determinants from the nonrepeat regions of Plasmodium falciparum LSA-1 in murine models and human subjects from areas where malaria is endemic in Rajasthan State, India. Seven peptide constructs (LS1.1 to LS1.7) corresponding to predicted T-cell sites from both the N-and C-terminal regions and peptide LS1R from a repea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 39 publications
2
19
0
1
Order By: Relevance
“…Studies of residents of South America, Papua New Guinea, India, and Africa have demonstrated varying frequencies of antibodies to LSA-1 synthetic peptides and recombinant proteins. 12,14,18,20,21,24 Unlike the current report, antibodies in these studies were evaluated at only one time point. The frequency of antibodies to LSA-Rep, a sequence that includes the EQ repeat evaluated in the current report, ranged from 17% in a non-immune population that migrated to a malaria- 14,24 Our finding that 32.1% of the individuals had IgG antibodies to a central repeat region peptide is in the mid-range of these prior studies.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Studies of residents of South America, Papua New Guinea, India, and Africa have demonstrated varying frequencies of antibodies to LSA-1 synthetic peptides and recombinant proteins. 12,14,18,20,21,24 Unlike the current report, antibodies in these studies were evaluated at only one time point. The frequency of antibodies to LSA-Rep, a sequence that includes the EQ repeat evaluated in the current report, ranged from 17% in a non-immune population that migrated to a malaria- 14,24 Our finding that 32.1% of the individuals had IgG antibodies to a central repeat region peptide is in the mid-range of these prior studies.…”
Section: Discussionmentioning
confidence: 89%
“…Reports from high transmission areas of India, Gabon, and Papua New Guinea showed that 59-82% of subjects had lymphocyte proliferation responses to LSA-1 peptides. 12,18,21 In contrast, studies examining residents of areas where transmission is low or studies restricting analysis to children who have not recently reported an attack of clinical malaria report lower response rates (6.7-33.1%). 14,20,22 A study of proliferation responses to LSA-1 in an highland area of Madagascar is most comparable to the current data.…”
Section: Discussionmentioning
confidence: 92%
“…These proteins are both surface proteins, and are expressed solely in infected hepatocytes and thought to have a role in liver schizogony and merozoite release. Specific humoral, cellular, and cytokine immune responses to LSA-1 and LSA-3 are well documented, with epitopes identified that correlate with the antibody production, proliferative T-cell responses, or cytokine induction (Aidoo et al, 2000;Joshi et al, 2000;Perlaza et al, 2001). Both preerythrocyte antigens have been considered to be vaccine candidates against P. falciparum due to their antigenic and protection-inducing immunogenic properties Kurtis et al, 2001;Sauzet et al, 2001;Taylor-Robinson, 2003).…”
Section: Usefulness Of the Recombinant Liver Stage Antigen-3 For An Ementioning
confidence: 99%
“…During this stage, the parasites express liver stage specific antigens. In P. falciparum, at least 2 of the relevant antigens, liver stage antigen-1 (LSA-1) and liver stage antigen-3 (LSA-3), have been identified and characterized (Guerin-Marchand et al, 1987;Aidoo et al, 2000;Joshi et al, 2000). These proteins are both surface proteins, and are expressed solely in infected hepatocytes and thought to have a role in liver schizogony and merozoite release.…”
Section: Usefulness Of the Recombinant Liver Stage Antigen-3 For An Ementioning
confidence: 99%
“…Analyses of the reactivity of specific antibody isotypes against these peptides were aimed to identify relevant B cell epitopes that could be used in a subunit vaccine (Joshi et al 2000, Tallima et al 2003. Synthetic peptides have been widely used for the evaluation of both B and T cell epitopes responsible for (or that could lead to) protection against other pathogens, including Schistosoma (Reynolds et al 1992, 1994, Eggleton et al 2000, Joshi et al 2000. We demonstrated that BALB/c mice vaccinated with SmCT-SOD developed high levels of antibodies directed mainly to the SmCT-SOD derived peptide 3 (Pep 3), which included amino acid residues 64-83 .…”
Section: Identification Of Parasite-specific Epitopesmentioning
confidence: 99%